USING THE DYNAMIC STOCHASTIC GENERAL EQUILIBRIUM (DSGE) MODEL TO MEASURE THE EFFECTIVENESS OF MONETARY POLICY IN THE FACE OF OIL SHOCKS - THE CASE OF IRAQ - Adnan Hadi Jaaz Al-Shammari; Raja Abdullah Issa Al-Salem (Scholar Express Journals, 2022)
This study seeks to track the impact of monetary policy in Iraq on facing various oil shocks, through the use of the General Stochastic Dynamics Model (DSGE) for the economic variables of Iraq after those models achieved important successes due to the development they witnessed. Econometric models developed significantly after the oil shocks of the 1970s, after the failure of traditional Keynesian models. One of the most important models that were developed to measure the impact of financial shocks is the dynamic general equilibrium (DSGE) models, which have become of great interest to most central banks in the world, which In its beginning, it was limited to measuring the effects of financial shocks on the economies of the industrialized oil-consuming countries, but today it is widely used by the rentier oil-producing countries. And Iraq as one of the countries that depend on oil exports, and oil rent constitutes more than 95% of the composition of its financial revenues, and that oil shocks have a severe impact on its economy in general, and therefore monetary policy had to play a role in absorbing the impact of these shocks, benefiting from the positive, and mitigating The negative impact of them, especially after the year (2004), which witnessed new laws that gave the Central Bank its independence in decision-making.
Keywords: Model; monetary policy; oil shocks,; positive